LEXICAL SEMANTIC ASPECTS OF SOMETIMES IN ENGLISH AND UZBEK LANGUAGE - Xakimova Gulsara Egamnazarovna; Jiyanova Jahona Ilhomovna (American Journals Publishing, 2024)
This article explores the lexical semantic nuances of the adverb "sometimes" in both English and Uzbek languages, shedding light on the cultural and linguistic variations that contribute to its usage. Through a comprehensive analysis, we aim to discern the subtle distinctions in meaning and usage, highlighting the impact of cultural and linguistic factors on the interpretation of temporal expressions.
Keywords: Lexical semantics, adverbs, temporal expressions, cross-linguistic analysis, english, uzbek, linguistic diversity.